BODIPY Catalyzes Proximity‐Dependent Histidine Labelling. Issue 9 (2nd March 2022) - Nakane, Keita; Niwa, Tatsuya; Tsushima, Michihiko; Tomoshige, Shusuke; Taguchi, Hideki; Nakamura, Hiroyuki; Ishikawa, Minoru; Sato, Shinichi
Abstract: The novel function of BODIPY, a widely used fluorescent probe, as a catalyst for the chemical labelling of histidine is revealed. Singlet oxygen ( 1 O2 ) produced by the photosensitizer property of BODIPY oxidises histidine residues, and the histidine oxidised by 1 O2 is trapped by the nucleophile 1‐methyl‐4‐arylurazole (MAUra). The simple chemical structure of BODIPY facilitates easier modification compared to other photosensitizer molecules and allows catalysis of protein/peptide‐labelling with higher histidine selectivity compared to the ruthenium complex. Owing to the short life of 1 O2, the reaction was selectively completed in close proximity with BODIPY. Site‐selective functionalization of the target/antibody was successfully achieved using ligand‐conjugated BODIPY. Abstract : BODIPY, a widely used fluorescent probe, functions as a photosensitizer and a catalyst for the chemical labelling of histidine. The histidine oxidised by 1 O2 is trapped by the nucleophile 1‐methyl‐4‐arylurazole (MAUra). The simple chemical structure of BODIPY allows catalysis of protein/peptide‐labelling with higher histidine selectivity.